On‐Demand Mode Conversion and Wavefront Shaping via On‐Chip Metasurfaces. Issue 23 (23rd September 2022) - Deng, Lin; Xu, Yihao; Jin, Renchao; Cai, Ziqiang; Liu, Yongmin
Abstract: In this work, mode conversion and wavefront shaping by integrating a metallic metasurface on top of a planar waveguide are proposed and demonstrated. The metasurface consists of C‐shaped nanoantennas. By controlling the orientation of each nanoantenna, mode conversion and focusing effect for the cross‐polarized electric fields inside the waveguide are achieved. The design and simulation results of 16 scenarios of wideband transverse‐magnetic to transverse‐electric mode converters with the mode purity up to 98%, and on‐chip lenses at the wavelength of 1550 nm are reported. It is worth noting that the dimension of the devices along the propagation direction is only 9.6 µm. This work manifests the potential application of mode division multiplexing systems and on‐chip optical interconnections based on metasurfaces. Abstract : This work reports a new platform that integrates a metallic metasurface on top of a planar waveguide. The mode conversion and focusing effects for the cross‐polarized electric fields inside the waveguide are achieved by controlling the orientation of C‐shaped nanoantennas in the metasurface. The research findings may lead to mode division multiplexing systems and on‐chip optical interconnections.